EFIKASI MENGAJAR GURU ANAK USIA DINI - Muflih Ma'mun; Dedy Achmad Kurniady; Nugraha Suharto (LPPM Sekolah Tinggi Agama Islam Darul Falah, 2021)
The teaching self-efficacy is an important aspect in improving student learning outcomes. The purpose of this study is to identify the level of efficacy of teaching early childhood teachers. This study used a survey approach to 27 preschool teachers in three sub-districts of Cihampelas through saturated sample techniques. The results of the study obtained an idea that the level of efficacy of teaching PAUD on the aspect of personal teaching efficacy including at the moderate level, and in general teaching efficacy included at a good level. To improve the efficacy of teaching, it can be done by developing competencies (seminars, workshops,training, etc.) or by carrying out lesson studies in schools.